Design Avionic Learning Media - VHF-HF Communication Based on Multimedia Animation on the ATKP - Abd Rachman Abubar; Hairul Amren; Eriansyah Saputra H; Iswandi Idris; Rizaldy Khair (LPPM Politeknik Aceh Selatan, 2020)
The importance of learning media and the development of technology is well-used Medan ATKP to continue to improve the quality of learning. The problem often encountered in avionic learning is the limited resource available because to access avionic learning the cadets must access from the LBT CBT and cannot be from elsewhere. This is because Avionic software is only installed in the lab and cannot be learned from outside the lab. The purpose of this study is to improve the digital avionic-VHF-HF Communication learning process that is packaged in multimedia animation to make it easier for cadets to learn avionic VHF-HF Communication without having access to a laboratory. The method used in this research is to use the Multimedia Development Life Cycle method, namely the Concept, Design, Material Collecting, Assembly, Testing, and Distribution. The resulting output is an animated video production and publication to journal.